Comparative analysis of switching losses and current ripple of continuous and discontinuous SVPWM strategies for unbalanced two‐phase four‐leg VSI Fed unsymmetrical two‐phase induction motor. Issue 3 (20th January 2021) - Muangthong, Kaset; Charumit, Chakrapong
Abstract: This paper presents a comparative analysis of the continuous space vector pulse width modulation and the discontinuous space vector pulse width modulation in terms of the switching losses and current ripple reduction for the unbalanced two‐phase four‐leg voltage source inverter fed unsymmetrical two‐phase induction motor. The main function of both space vector pulse width modulation strategies is to produce unbalanced two‐output voltages with constant phase shift of 90° for main and auxiliary windings. The discontinuous space vector pulse width modulation principle is modified from a traditional two‐phase four‐leg voltage source inverter by placement of the space vectors to alternatively eliminate zero space vector in each switching sequence. As a consequence, the proposed unmodulation region or clamping zone of the discontinuous modulation strategy has 180° all the time. The experimental results illustrate the modulation waveforms of both methods, output voltage spectrum, normalized switching losses, output current ripple and inverter efficiency at high modulation index. The evaluation of the normalized average switching losses and the current ripple of the discontinuous space vector pulse width modulation method can be reduced more than that of the continuous space vector pulse width modulation method.